The Effectiveness Of Flashcard-Based Instruction In Enhancing English Vocabulary Mastery Among EFL Learners: A Systematic Literature Review - Sofi Yatul Ilmah; Zahro Salsabila; Arif Purnama; Elyza Martiarini (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Vocabulary mastery is a core component of English language proficiency, particularly for English as a Foreign Language (EFL) learners who have limited exposure to authentic language input. A lack of vocabulary knowledge often restricts learners’ ability to understand texts and communicate ideas effectively. One instructional strategy that has been widely applied to address this issue is flashcard-based instruction, which emphasizes repeated exposure and active recall to support vocabulary retention. This study aims to examine the effectiveness of flashcard-based instruction in enhancing English vocabulary mastery among EFL learners through a systematic literature review. The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a transparent and systematic research process. Data were collected from peer-reviewed journal articles published between 2020 and 2025 and retrieved via Google Scholar. After the processes of identification, screening, and eligibility assessment, 30 relevant studies were selected for analysis. The findings reveal that flashcard-based instruction has a positive impact on learners’ vocabulary development, with digital flashcards showing higher effectiveness due to the integration of multimedia features and spaced repetition systems. The study concludes that flashcard-based instruction is an effective and practical approach for improving English vocabulary mastery in EFL contexts.